Analisa Kebijakan Penerimaan WNI Mantan Simpatisan ISIS di Suriah - Sumawiharja , Farhan Arif; Adis Imam Ismunandar, Adis Imam Ismunandar (Jurnal Keamanan Nasional, 2020)
Radicalism and terrorism are becoming a global problem. The negative impact is often felt by Indonesia. Several terror acts also occur and cause any casualties. ISIS developments in the world attract people to join the majority of Indonesian people. But after the defeat of ISIS 2019 ISIS ex citizen has the desire to return to Indonesia. ISIS former citizens accepted into a dilemma, but the policy must still be taken by the government in order to maintain national security and stability. The present study used qualitative methods and review of the literature as well as the approach Stakeholders Analysis. ISIS's former citizen admission policy has been set, but the human side must also be considered. Then more synchronous data updates the main requirements and terms of absolute acceptance of ex-Asian citizen who mostly are children and women.